Acceptance and use of smart home technologies: A focus on Portugal - Domingues, J.; Ferreira da Silva, C. (Web Information Systems Engineering – WISE 2024: 25th International Conference, Proceedings, Part III, 2024)
In this study, the authors access the acceptance and perception of usage of Smart Home Technologies (SHTs) within a sample of a survey respondents in Portugal. The primary research goal focuses on the factors influencing the decision to embrace or shy away from these technologies in the Portuguese setting. Such research involved understanding motivations, challenges, barriers, and the perceived pros and cons of integrating these tools into daily life. To achieve this, our methodological approach blends qualitative and quantitative methods. The qualitative method, supported on a systematic literature review that serves as a guide to the elaboration of our survey questionnaire, and also allows the comparison of different geographical SHTs adoption patterns reported in several studies. Our quantitative analysis is supported by an online survey questionnaire rooted in the extended Technology Acceptance Model and the analysis of research hypotheses. The growing interest in SHTs in Portugal is driven by the search for greater quality of life and efficiency. Findings also highlight the appreciation for the cost-saving, security, and energy efficiency offered by such technologies (SHTs). Additionally, these were also noted for their ability to automate tasks, enhance the quality of life, improve comfort, and provide remote device control, thereby cutting down time and effort in daily activities. However, despite the apparent benefits of these technologies, their adoption varies; while many have integrated SHTs into their routines, a notable segment remains hesitant, namely due to concerns about data control, privacy and trust.